Location-based information systems developing real-time tracking applications - Labrador, Miguel A. (CRC Press, 2011)
"The book provides a comprehensive introduction to developing location-based information systems based on GPS-enabled cellular phones. It describes all of the components needed to develop a location-based information system and provides readers with the opportunity to build an example application. Chapters cover obtaining a user's location, storing and retrieving data, communicating over a network, Java ME Web services, and visualizing data. In the theoretical chapters, the authors address location provider architectures, the hardware and software architecture of a mobile phone, the Java ME platform, and other important programming aspects for mobile phones"-- Provided by publisher.
Keywords: Location-based services.; elektronické knihy; electronic books